Erosive softening and erosive loss of enamel: Hardness and profilometry analysis - Priscila Maria Aranda Salomão; Daiana Moreli Soares dos Santos; Camila Perfeito Evangelista da Silva; Marília Afonso Rabelo Buzalaf; Annette Wiegand; Ana Carolina Magalhães (Brazilian Dental Science)
Objective – This study aimed to determine and differentiate erosive softening and enamel erosive loss induced by citric and hydrochloric acids. Material and Methods – Forty enamel specimens were divided into 2 groups: 1) 0.05 M citric acid (pH 2.5) simulating extrinsic erosion and 2) 0.01 M hydrochloric acid (pH 2.2) simulating intrinsic erosion. The enamel specimens were submitted to erosive challenges. Surface microhardness (softening) or contact profilometry (loss) was done after 30 s, after each 60 s up to 10 min, after each 5 min up to 30 min and after 60, 90 and 120 min. Results – Erosive softening (enamel hardness loss) was measurable up to 1 and 2 min for hydrochloric and citric acids, respectively. Erosive loss was significantly increased over time for both types of acids. After 8 min, citric acid was more aggressive than hydrochloric acid (p < 0.001). Conclusion – The progression of enamel erosion from erosive softening to erosive loss is highly dependent on the type of acid, being citric acid more aggressive in later stages. Therefore, this finding should be considered when choosing the method of analysis for laboratory studies.